Sources of German unemployment: A structural vector error correction analysis - Ralf Brüggemann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
In this paper we analyze the sources of German unemployment within a structural vector error correction model (SVECM) framework. For this purpose, we propose a method to estimate an exactly identified Subset SVECM, which is a SVECM with short run parameter restrictions. A cointegration analysis for the unified Germany reveals a long rum relationship between real wages, productivity and unemployment which is interpreted as a wage setting relation. From a Subset VECM we identify meaningful structural shocks and assess their importance for unemployment by impulse response analysis and forecast error variance decompositions. We compare these results to results from a standard SVECM and find that, using the Subset VECM reduces estimation uncertainty. In contrast to previous studies for West Germany, we find that, unemployment is equally determined by technology, labor supply and labor demand shocks in the long run. - Unemployment ; Subset VECM ; Structural VECM ; Bootstrap ; Cointegration
urn:nbn:de:kobv:11-10049387
Keywords: C32; E24; 330